TINJAUAN KEBUTUHAN SDMK INSTALASI REKAM MEDIS BERDASARKAN METODE ABK-KES DI RSUD BANJARNEGARA - Arum Astika Sari; Yektiningtyastuti; Raudya Tuzzahra; Agus Subechi (Jurnal Kesehatan dan Pembangunan, 2026)
ABSTRAK Proper planning of health human resources (HHR) is essential to support the quality and efficiency of medical record services in hospitals. A mismatch between workload and staffing levels has the potential to reduce the quality of medical record management. This study aims to analyze HHR needs at the Medical Records Unit of RSUD Hj. Anna Lasmanah Banjarnegara using the Health Workload Analysis (ABK-Kes) method. This study is a quantitative research with descriptive analytic design. Data were collected through observation, interviews, and document review, then analyzed based on the ABK-Kes calculation guidelines of the Ministry of Health of the Republic of Indonesia. The results showed that the HHR needs in the Outpatient Registration Unit, Inpatient Unit, and Emergency Unit were 7 people, the Assembling Unit 7 people, the Indexing Unit 3 people, the Coding Unit 7 people, and the Filing Unit 8 people. An imbalance in the distribution of HHR was found, where the registration unit had excess personnel, while the assembling, indexing, coding, and filing units experienced a lack of personnel, which is an indication that the planning and distribution of HHR in the Medical Records Installation is not yet optimal. Adjustments and redistribution of HHR based on actual workload are needed to improve the efficiency and quality of medical record services.